Effect of three insecticides on Post Embryonic development, egg production and body weight of Rhynocoris longifrons (Stal) (Insecta: Hemiptera: Reduviidae) - George, P.J. Edward (International Journal of Environment, Agriculture and Biotechnology, 2024)
Post embroyonic development time egg production rate and body weight of Rhynocoris longifrons (Stal°) were studied for three commonly used insecticides in the agro ecosystem namely monocrotophos, dimethoate and quinalphos. All of the instecticides increased and stadial period and decreased the body weight, egg production and longevity. Maximum effect of the insecticides was observed in monocrotophos treated insects which was followed by dimethoate and quinalphos applied insects. This study paves an idea that while applying the insecticides in the agro ecosystem to control insect pests, care should be taken in the selection of insecticides which will be safe to the non-target insects which is already available in the ecosystem.